2010
DOI: 10.4061/2010/348919
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melatonin on Adrenal Cortical Functions of Indian Goats under Thermal Stress

Abstract: The study was conducted with the primary objective to establish the influence of melatonin on adrenocortical functions to ameliorate thermal stress in goats. Endocrine secretions and several other blood biochemical parameters reflecting the animals adrenocortical stress response were determined over a one-week period after goats had been exposed to 40°C and 60%RH for 10 days. The study was conducted for a period of 17 days in psychrometric chamber. The animals served as self-controls prior to start of the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 35 publications
(40 reference statements)
4
30
1
Order By: Relevance
“…Plasma glucose decreased significantly in GII, GIII, and GIV ewes as compared to control ewes, with the greatest decrease being seen in the combined stress group. Several researchers have studied the effect of thermal stress on blood glucose concentrations but conflicting results have been reported (More and Sahni 1980;Habeeb 1987;Sejian and Srivastava 2010). The decrease in plasma glucose could also be due to the marked dilution of blood or increase in plasma glucose utilization to produce more energy for the greater muscular expenditure required for high muscular activity (Naqvi and Hooda 1991;Rasooli et al 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Plasma glucose decreased significantly in GII, GIII, and GIV ewes as compared to control ewes, with the greatest decrease being seen in the combined stress group. Several researchers have studied the effect of thermal stress on blood glucose concentrations but conflicting results have been reported (More and Sahni 1980;Habeeb 1987;Sejian and Srivastava 2010). The decrease in plasma glucose could also be due to the marked dilution of blood or increase in plasma glucose utilization to produce more energy for the greater muscular expenditure required for high muscular activity (Naqvi and Hooda 1991;Rasooli et al 2004).…”
Section: Discussionmentioning
confidence: 94%
“…The light microscopic examination of the semithin sections of the testis of the hypothyroidic group (group 4) revealed seminiferous tubules with lumen devoid of spermatozoa and obliterated seminiferous tubules lumina with debris (Figs. 19,21). Additionally, some tubules were lined by disorganized germ cells with empty spaces in between the cells (Fig.…”
Section: Hypothyroidic Group (Group 4)mentioning
confidence: 94%
“…An oedematous interstitial tissue among the tubules revealing dilated blood vessel and shrunken darkly stained Leydig cells were observed (Figs. [19][20][21].…”
Section: Hypothyroidic Group (Group 4)mentioning
confidence: 99%
“…Our earlier findings also revealed that these buffalo PP and peptides have certain physiological functions viz. immunopotentiation,12 heat stress,13 amelioration of fluoride-induced OS and apoptosis 8,14. These proteins have a geroprotective effect which might be due to their free radical scavenging ability and thus antioxidant properties 15,16.…”
Section: Introductionmentioning
confidence: 99%